Do Danish voters discriminate against women and ethnic minority candidates? Insights from a survey experiment - Laustsen, Lasse; Gothreau, Claire (Politica, 2023)
Representation of women and ethnic minorities is a recurring topic in connection with Danish elections. One possible explanation for the consistent underrepresentation is that voters evaluate women and ethnic minority candidates less favorably than men with an ethnic Danish background. Theoretically, this possibility might be particularly pronounced among conservative voters high in Social Dominance Orientation (SDO). Analyses from a survey experiment with 1116 representative Danish citizens show that Danes, on average, do not evaluate women and ethnic minority candidates less favorably. However, nuanced exploratory analyses show that growing SDO and conservatism cause voters to evaluate ethnic minority candidates more negatively, while a similar pattern does not obtain with respect to candidate gender. Consequently, issues about underrepresentation of women and ethnic minorities relate differently to SDO and political ideology. The theoretical and normative implications of the results are discussed.